Inventory of Educational Facilities and Infrastructure - Mardiah Astuti; Icha Suryana; Marwansyah Marwansyah; Gina Inez Zyfana; Dinda Aisyah Aulidya Putri; Okky Nadia (Sustainable, 2023)
This research uses a descriptive qualitative approach to describe educational facilities and infrastructure inventory. Facilities and infrastructure are all the resources and tools a school or educational institution owns to support school activities or assist the teaching and learning process. This is very important to achieve school educational goals. Therefore, these facilities and infrastructure must be maintained to help achieve academic goals. "inventory" refers to activities related to inventory items, such as their management, organization, recording, and registration. The method for maintaining the quality and quantity of facilities and infrastructure is Inventory. Therefore, its implementation will be critical. Therefore, understanding how to do it correctly and regularly is very important.